Juventude sobre pressão: um fórum alemão e uma obra de Octávio Ianni - Caccia-Bava Júnior, Augusto [UNESP] (My University, 2010)
In the 20th century, youth has become a western myth rather than an important social category in the projection of future societies. The Right-wing was ahead of left-wing movements supporting national political projects. The crisis in the Welfare state and socialism system disoriented the right and left-wing movements. The myth of youth as reference for the progressive development of history was destroyed. Youth movements, consolidated in some student movements and supported by some religious organizations took over this reference position. However, these new youth movements are rarely engaged in political or environmentalist projects. The violence that originates from disturbing practices of social reproduction puts youth under pressure.

A juventude constituiu-se como mito ocidental, antes que categoria social importante para a projeção do futuro das sociedades. A direita antecedeu a esquerda na busca de seu envolvimento em projetos políticos nacionais. A direita e a esquerda, sem norte claro, após as crises do welfare state e do sistema socialista dissolveram o mito e a juventude, como referência de desenvolvimento progressivo da história. Hoje encontramos movimentos juvenil, consolidados em algumas organizações estudantis, tutelados em algumas organizações religiosas, afinados em poucos projetos políticos partidários, ou ambientalistas. Mas o que mais os envolvem é a violência urbana.
Keywords: Youth myths; Urban violence; Social reproduction; defesa da cidadania; Direito dos jovens; Globalização; resistência; Violência urbana